36‐month data for the AdVance XP® male sling: results of a prospective multicentre study. (2nd December 2016) - Bauer, Ricarda M.; Grabbert, Markus T.; Klehr, Benedikt; Gebhartl, Peter; Gozzi, Christian; Homberg, Roland; May, Florian; Rehder, Peter; Stief, Christian G.; Kretschmer, Alexander
Abstract : Objectives: To evaluate the efficacy and safety of the AdVance XP ® sling (Boston Scientific, formerly American Medical Systems) in male stress urinary incontinence (SUI) after radical prostatectomy in a prospective multicentre study, as in recent years several studies have shown the effectiveness and safety of the AdVance sling for treating male SUI and in 2010 the second‐generation AdVance XP was introduced with several changes in the sling design and a new needle shape. Patients and Methods: In all, 115 patients were included. Patients with nocturnal UI, previous UI surgery, previous radiotherapy and a coaptive zone of <1 cm in the preoperative repositioning test were excluded. Postoperatively, a standardised 24‐h pad test, quality‐of‐life scores [International Quality of Life score (IQOL) and International Consultation on Incontinence Questionnaire short form (ICIQ‐UI SF)], visual analogue scale (VAS) for pain, five‐item version of the International Index of Erectile Function (IIEF‐5), International Prostate Symptom Score (IPSS) and Patient Global Impression of Improvement (PGI‐I) score, were performed. All patients with a 0–5 g pad test were defined as cured and improved with a reduction of urine loss of >50%. All others were classified as failures. Significance analysis was performed using the Wilcoxon test. Results: The mean (median) preoperative urine loss in the 24‐h pad test was 272.0 (272.0) g. After a follow‐up of 3 months (114 patients), 64.9% of the patients were cured and 31.6% had an improved continence status. The mean urine loss decreased significantly to 34.9 g ( P < 0.001), with a mean VAS score of 0.5, and mean PGI‐I of 1.5. After a follow‐up of 24 months (80 patients), 68.8% of the patients were cured and 22.5% had improved. The mean urine loss decreased significantly to 19.1 g ( P < 0.001), with a mean VAS score of 0.3, and mean PGI‐I of 1.5. After a follow‐up of 36 months (47 patients), 66.0% of the patients were cured and 23.4% had improved. The mean urine loss decreased significantly to 21.8 g ( P < 0.001), with a mean VAS score of 0.0, and mean PGI‐I of 1.6. The mean IQOL and ICIQ‐UI SF improved significantly (both P < 0.001) after 36 months. There were no significant postoperative changes in IIEF‐5 and IPSS. No intraoperative and no long‐term complications occurred. No erosion or explanations occurred. Conclusion: The AdVance XP shows good and stable effectiveness and low complication rates even at a mid‐term follow‐up of up to 36 months.